High-Energy Emission from Accreting Black Holes with High-Mass Donor Stars - Vila, Gabriela Soledad (2008)
We present an analysis of the interactions of a distibution of relativistic protons under the typical conditions of the corona surrounding an accreting black hole. The model is applied to a concrete binary system with a high-mass donor star: the classical source Cygnus X-1.